What explains the variation on the regenerative component dynamics of Araucaria Forests in Southern Brazil? - Vefago M.B.* (2019)
© 2019, Scientia Agricola. All rights reserved.The natural regeneration process is essential for forest maintenance since it is critical for establishing new tree individuals. This study aimed to improve the understanding of the regenerative component dynamics of Araucaria Forests in Southern Brazil. We investigated the effects of climate, light, tree component structure and anthropogenic disturbance on tree species regeneration. Regenerating communities from six different fragments in forest remnants of the “Planalto Sul Catarinense” region was evaluated in permanent plots two years after the first inventory. The following demographic rates were determined: recruitment, mortality, net change in the number of individuals and the changes to both upper and lower height classes. The following variables were measured in each fragment: altitude, climatic variables, light environment, tree component density and cattle presence. Association between dynamics rates, regenerating species abundance and explanatory variables was verified by the fourth-corner and RLQ methods. A total of 4,379 and 5,268 individuals were sampled for the first and second inventories, respectively, with recruitment rate (21 % yr-1) higher than mortality rate (13 % yr-1). The dynamics pattern of the fragment with greater presence of cattle stood out for the intense height increase of regenerating species caused by the presence of fast growth and light-demanding species. Natural regeneration of forest remnants under study is facing a structuring process. The main conclusions of this study were: i) climate and altitude play a relevant role in defining floristic identity and ii) chronic disturbances may influence the definition of ecological strategies.